2017
DOI: 10.1007/s00586-017-4959-0
|View full text |Cite
|
Sign up to set email alerts
|

Teriparatide versus low-dose bisphosphonates before and after surgery for adult spinal deformity in female Japanese patients with osteoporosis

Abstract: Perioperative administration of teriparatide is more effective than that of low-dose bisphosphonates in preventing complications and maintaining fusion rates in osteoporotic Japanese females with spinal deformities undergoing surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 19 publications
4
73
0
Order By: Relevance
“…found that adjacent vertebral fracture, implant failure, and fusion failure rates were signi cantly lower in their TP group than in their BP group [16]. In accordance with these studies, our result also suggested that it may be considered useful for reducing mechanical complications and pseudoarthrosis in surgically treated case of OVF.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…found that adjacent vertebral fracture, implant failure, and fusion failure rates were signi cantly lower in their TP group than in their BP group [16]. In accordance with these studies, our result also suggested that it may be considered useful for reducing mechanical complications and pseudoarthrosis in surgically treated case of OVF.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have demonstrated the superiority of TP over BP in patients who have undergone conservative treatment for OVF according to bone union rates [13][14][15]. Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [16][17][18][19][20][21]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of TP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative treatment with recombinant human parathyroid hormone (teriparatide/Forteo) has been useful for preoperative augmentation of bone quality, with good outcomes in patients with poor bone mineral density scores. This drug not only has antiresorptive but also osteoinductive properties that quickly re-establish good bone quality in patients requiring major spinal deformity surgery (7)(8)(9)(10)(11)(12).…”
Section: Patient Selectionmentioning
confidence: 99%
“…Previous studies have demonstrated the superiority of TP over BP in patients who have undergone conservative treatment for OVF according to bone union rates [12][13][14]. Other studies have shown the positive effects of TP on bony fusion after spinal fusion or correction surgery [15][16][17][18][19][20]. TP has bone anabolic ability and can reduce the chance of screw loosening, and so the use of BP may effectively enhance spinal fusion and reduce implant failure and/ or subsequent vertebral fracture in comparison with surgery [16,19,20].…”
Section: Introductionmentioning
confidence: 99%